Coronavirus disease 2019 (COVID‐19) in two pediatric patients with kidney disease on chronic immunosuppression: A case series. Issue 1 (5th October 2020) - Rawson, Ashley; Wilson, Amy C.; Schwaderer, Andrew L.; Spiwak, Elizabeth; Johnston, Bethanne; Anderson, Shannon; Nailescu, Corina; Gupta, Sushil; Christenson, John C.; Hains, David S.; Starr, Michelle C.
ABSTRACT: Coronavirus disease 2019 (COVID‐19) is a highly infectious disease caused by the severe acute respiratory syndrome coronavirus 2 virus (SARS‐CoV‐2). While children appear to experience less severe disease than adults, those with underlying conditions such as kidney disease may be more susceptible to infection. Limited data are present for children with kidney disease, and there are limited prior reports of pediatric hemodialysis patients with COVID‐19. This report describes the mild clinical disease course of COVID‐19 in two pediatric patients with chronic kidney disease, one on hemodialysis and both on chronic immunosuppression. We review treatment in these patients, as well as our measures to reduce transmission among our hemodialysis patients and staff.